The Effect of Computer Games on Intelligence Quotient, Reaction Time, and Movement Time of Adolescents - Masoud delbari; Hasan Mohamadzade; Mahmud Delbari (University of Tehran, 2009)
The aim of this study was to investigate the effect of computer games on intelligence quotient (IQ), reaction time (RT), and movement time (MT) of adolescents. The statistical population of this study consisted of male high school students (aged between 14 and 18), Restrict 1 in Tabriz city. Two samples (n1=n2=25) were selected purposefully and were divided into two equivalent groups (experimental and control). The experimental criterion was to play computer games a minimum of three days a week for the past six months. The control group played little or preferably no computer games in the past six months. To determine their IQ, Cattle's intelligence test (Scale 3) and normative tables were used. RT and MT of subjects were measured by appraiser system of RT and MT. Results showed that computer games had a significant effect on IQ (P=0.031), simple reaction time (P=0.017), simple movement time (P=0.019), diagnostic time (P=0.04) and diagnostic movement time (P=0.036). Also findings established that the computer game experience improves IQ, reaction times and movement times.